Penerapan Model Antrean FIFO untuk Meningkatkan Efisiensi Pelayanan pada Bank Mini Syari’ah di Pondok Pesantren Syalafiyah Syafi’iyah Sukorejo - ABD. Ghofur; Nadhrotun Jamilah; Ana Putri Nur Amanah; Jannatin Firdausiyah; Mardhiyatul Jazilah (CV. ALIM'SPUBLISHING, 2026)
This research examines the operational dynamics of the First In First Out (FIFO) queuing approach at the Bank Mini Syari'ah unit of Pondok Pesantren Salafiyah Syafi'iyah Sukorejo, a pesantren-run financial service handling santri's day-to-day transactions. Long queues remain common in Islamic financial institutions, often persisting even after FIFO is formally adopted, leaving customer dissatisfaction largely unresolved. This research describes how FIFO is designed, applied, and interpreted by Customer Service staff and santri within the pesantren's distinct social setting. A descriptive qualitative method was used, drawing data from in-depth interviews, direct observation of daily queue behavior, and transaction documentation dated 20 June 2026. Data were processed through interactive analysis following Spradley and Miles-Huberman, with credibility secured via source and technique triangulation. Results show FIFO realized through a Java-based program separating Teller and Customer Service queues; field testing revealed transaction peaks clustered in mid-morning hours while officer workloads stayed fairly balanced. The study finds FIFO improves order over the earlier informal